Effectiveness and Efficiency of Mediation in Out-of-Court Dispute Settlement as an Alternative Legal Protection for Disputing Parties - Nasution, Izhar Zahri; Redi, Ahmad (Greenation Publisher & Yayasan Global Resarch National, 2025)
Mediation as an alternative form of dispute resolution outside the court is increasingly gaining attention in the Indonesian legal system. This study aims to analyze the effectiveness and efficiency of mediation in providing legal protection for disputing parties without going through a long, expensive litigation process that often causes prolonged conflict. Through a normative legal approach with literature studies and analysis of mediation regulations and practices in various institutions, it was found that mediation offers faster, more flexible solutions that pay attention to common interests. The results find that the success of mediation is highly dependent on the mediator's quality, the willingness of the parties, and adequate regulatory support. Thus, mediation can be an effective and efficient means of resolving disputes while strengthening access to justice for the community.